1970
DOI: 10.1021/je60047a017
|View full text |Cite
|
Sign up to set email alerts
|

Saturation pressures of cesium to temperatures and pressures approaching critical state

Abstract: Saturation pressures were experimentally extended for cesium with use of a static method and a tantalum-alloy apparatus with a metal diaphragm as a pressuresensing device. Vapor pressure equations of the Kirchhoff-type accurately represent the observed data for an extended temperature range from the normal boiling point to 3026°F , and the log T term is shown statistically to be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1971
1971
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Metallic fluids, and in particular those of the alkali metals, are of great interest in many space and nuclear power programs where coolants and working fluids are required at high temperatures. Thermophysical properties of saturated and superheated phases are needed for the design and development of these power systems. , The anticipated use of alkali metals of working fluids, heat transfer media, and lubricants in high-temperature energy-conversion systems has spurred considerable research on the thermophysical properties similar to the surface tension of these fluids. , The main industrial use for lithium is in ceramics, glass, and aluminum production, but its use in electric batteries and as a heat carrier in atomic fusion reactors will increase the demand …”
Section: Introductionmentioning
confidence: 99%
“…Metallic fluids, and in particular those of the alkali metals, are of great interest in many space and nuclear power programs where coolants and working fluids are required at high temperatures. Thermophysical properties of saturated and superheated phases are needed for the design and development of these power systems. , The anticipated use of alkali metals of working fluids, heat transfer media, and lubricants in high-temperature energy-conversion systems has spurred considerable research on the thermophysical properties similar to the surface tension of these fluids. , The main industrial use for lithium is in ceramics, glass, and aluminum production, but its use in electric batteries and as a heat carrier in atomic fusion reactors will increase the demand …”
Section: Introductionmentioning
confidence: 99%
“…Recent technological advances have yielded increased applications for the alkali metals. An accurate knowledge of the physical properties of these fluids has become vital in many of these applications. X-ray diffraction and small-angle X-ray scattering of rubidium fluids have been measured by reducing electron density down to the range where the compressibility of the interacting electron gas has been theoretically predicted to become negative. It suggests that an attractive interaction among like charges, ions in this case, is enhanced .…”
Section: Introductionmentioning
confidence: 99%
“…16 Considering the internal pressure by modeling the average configurational potential energy and then taking its derivative with respect to volume predicts that the isotherm ((∂E/∂V) T /FRT)V 2 is a linear function of F 2 , where E is the internal energy and (∂E/∂V) T is the internal pressure. 17 The final result is therefore of the form (Z -1)V 2 ) A + BF 2 (1)…”
Section: Introductionmentioning
confidence: 99%
“…The objective of the present program was to extend this work to the critical state for cesium by additional PVT measurements at higher temperatures. This article follows the reporting of saturation pressures (4).…”
mentioning
confidence: 95%
“…PVT Properties of Cesium one recorded point in the superheat range. Another point, at 3182.5°F and 106.11 atm, was initially recorded as superheat data, but subsequent analysis has shown that this point is near the intersection of the saturation and superheat curves where pressures are known to be severely depressed(4,24). Consequently, this point is not recorded in TableIIand is given no weight in the development of the equation of state.…”
mentioning
confidence: 99%